A study on the readiness of university students to use E-Learning Tool : a case study of University Teknologi Malaysia, Skudai Johor - Mohd. Balwi, Mohd. Koharuddin; Idrus, Durrishah; Mursib, Gurupiah; Md. Junoh, Adnan; Bunari, Ghazali; Abdul Hamid, Mohd. Azhar; Bakri, Mohd. Sharil (Faculty of Management and Human Resource Development, 2004)
This research want to identify the level of awareness and readiness among Universiti Teknologi Malaysia students on the e-leaming program implimented by the university. The study will focus on the level of application of e-learning in the daily lives of the students. This study also want to identify the factors that influenced students to using elearning in their learning process. This research also investigate the various problems that students face in using the e-leaming application. This study focus on the e-learning initiative by the Universiti Teknologi Malaysia, Skudai, Johor Bahru, Johor only. Respondents chosen from every faculty and involving only undergraduate students. Three objective of the research were designed, one : to identify the level of awareness, readiness, and usage of the e-leaming program among the students, two : to identify the factors which influenced students to using e-leaming program and three : to investigate the various problems that students face in using the e-leaming application. The conclusion for this study was the level o f the awareness, readiness, and usage of elearning application among university students were moderate.